Is There Decreasing Prevalence of Helicobacter Pylori Infection in Patients with Dyspepsia? (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Word-wide there is decreasing prevalence of Helicobacter pylori (H. Pylori) infection. As we are lacking in consistent data regarding H. Pylori infection in our polpulation, we aimed to find out prevalence of H.pylori infection in patients with dyspepsia in Nort-East part of Bangladesh.  Material and methods: Clinical variables, stool antigen test result and endoscopic findings of consecutive patients with dyspepsia were recorded in a semi-structured questionnaire. Statistical analysis was done with SPSS programme 17.0(). Significance level was set at 0.05 or less.Results: A toal of 790 patients (male 549, female 241) were included in the study with higher mean age among female patients (41.46 VS. 39.19, p.008) than male patients. Three most common dyspetic symptoms were abdominel pain (n=365, 46.2%), bloating (n=280, 35.4%) and vomiting (n=163, 20.6%). A total of 217(39.5%) male and 87(36.0%) female were positive for stool antigen test (n=308, 38.5%) for H. pylori. No significant association was found between Helicobacter pylori infection and presence of individual dyspeptic symptom, number of dyspeptic symptoms (OR 1.385, p .103), age (OR .998, p .668), sex (OR 1.157, p .362), rural/urban residence (OR 1.126, p .503) or socioeconomic condition (OR .965, p .09).  Around 81% (293/360) subjects had upper GI lesion (Gastritis/gastric ulcer, duoudenitis/duodenalulcer, oesophagitis/ulcer) in endoscopy and stool antigent positivity in paietnts with duodenal and gastric lesions (37% VS. 36.6%) were comparable.Conclusion: H. pylori infection rate among patients with dyspepsia is is in favour of declining prevalence of H.pylori infection in comparison to previous sudies. Majority of patients with dyspepsia had upperGI lesion in endoscopy. No sigficant differece was noted in H. pyori prevalence rate anong gastric or duodenal lesion or among PPI takers or non-takers.JCMCTA 2022 ; 33 (1) : 97-102